PENGARUH PERSEPSI SISWA TENTANG BIMBINGAN BELAJAR DAN MOTIVASI TERHADAP HASIL BELAJAR SISWA KELAS V DI SDN WIROBORANG 4 KOTA PROBOLINGGO TAHUN PELAJARAN 2014-2015 - Andy Dwi Cahyono (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This research aims to know the influence of students’ perception of tutoring and motivation on learning achievement of fifth graders at SDN 4 Probolinggo. Ninety two (92) students were invoked as respondents in this research. As the result, it showed that there was an influence on tutoring and learning achievement, learning motivation and learning achievement, tutoring and learning motivation simultaneously on learning achievement of fifth graders at SDN 4 Probolinggo.